Novel mutation of the P0 extracellular domain causes a Déjérine-Sottas syndrome. Issue 3 (1st March 1999) - Fabrizi, Gian Maria; Cavallaro, Tiziana; Morbin, Michela; Simonati, Alessandro; Taioli, Federica; Rizzuto, Nicolo'
Abstract : A patient is described with a Déjérine-Sottas syndrome caused by a novel heterozygous Cys(98)Tyr mutation in the extracellular domain of the major peripheral myelin protein zero (P0ex). Homotypical interactions between P0ex tetramers of apposed extracellular faces of the Schwann cell membrane play a crucial part in myelin compaction. The amino acid change disrupts a unique disulphide bond that stabilises the immunoglobulin-like structure of P0ex and it is predicted to cause severe de-hypomyelination through dominant negative effects on the wild type protein.